2011
DOI: 10.1093/ndt/gfr214
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sirolimus, tacrolimus and mycophenolate mofetil on osteoclastogenesis--implications for post-transplantation bone disease

Abstract: Taken together, SRL was shown to inhibit osteoclast formation in vivo and in vitro. SRL thus may have the potential to balance osteoclast promoting effects of glucocorticoids and CI, thereby counteracting the development of accelerated osteoporosis in renal transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 39 publications
6
42
1
2
Order By: Relevance
“…So we concluded that TAC could induce bone disorders in kidney transplant recipients and accelerate bone resorption. Our results were in agreement with a recent study from Westenfeld et al [21]. The possible mechanism of TAC on bone mainly due to the resorption exceeded formation involving the imbalance of RANK-RANKL-OPG system [9,21] or partly by inhibiting ERK 1/2 [8].…”
Section: Discussionsupporting
confidence: 94%
“…So we concluded that TAC could induce bone disorders in kidney transplant recipients and accelerate bone resorption. Our results were in agreement with a recent study from Westenfeld et al [21]. The possible mechanism of TAC on bone mainly due to the resorption exceeded formation involving the imbalance of RANK-RANKL-OPG system [9,21] or partly by inhibiting ERK 1/2 [8].…”
Section: Discussionsupporting
confidence: 94%
“…Steroids directly worsen bone formation by impaired genesis and increased apoptosis of osteoblasts and enhanced osteoclastogenesis through an increased RANKL/OPG ratio [30] . Both cyclosporin and tacrolimus similarly promote bone loss via direct osteoclast activation [58] , but sirolimus is administered as a bone-sparing immunosuppressive agent due to its capability to inhibit osteoclast generation [57,59] .…”
Section: Ptbd: Epidemiology and Mechanismsmentioning
confidence: 99%
“…Some studies suggest a relationship between VC and impaired bone metabolism as well as an involvement of immunosuppressive drugs on expression, regulation, and function of RANKL, RANK, and OPG system working in skeletal and vascular systems. In particular, sirolimus inhibits osteoclast formation, unlike steroids and cyclosporine [56]. …”
Section: Progression Risk Factorsmentioning
confidence: 99%